PLATFORMISING STORYTELLING: SHORT FICTION, NEOLIBERAL IMMEDIACY, AND TWITCH STREAMING IN ROMANIA - VIȘAN, Bogdan; DANIELESCU, Ioana (Studia Universitatis Babeș-Bolyai Philologia, 2025)
Platformising Storytelling: Short Fiction, Neoliberal Immediacy, and Twitch Streaming in Romania. In light of the neoliberal ascent of platform capitalism, storytelling is undergoing an unmatched metamorphosis noticeable even in semi-peripheral cultures, including Romania’s. From a methodological standpoint, we examine these literary and cultural transformations by situating a particular case study within the ideological frameworks of neoliberal capitalism as it manifests on streaming platforms. Our case study focuses on reallyrux’s Twitch and YouTube series “Cine-i janghina?” (“Who’s the Asshole?”), where audiences submit allegedly autobiographical short stories based on preestablished themes, focused on multi-sided conflicts. The host reads and discusses the stories in live streams, playfully evaluating their style while suggesting that the show enhances her audience’s literary knowledge, thus positioning the series as both participatory entertainment and an informal workshop. Consequently, the study’s aim is three-fold: first, to analyse the interrelationship between the literary and the digital, in particular, platform-based content; second, to investigate the revitalisation of the short story genre through participatory digital practices in the context of the prevalent trend of creative writing workshops in Romania; and third, to assess the immediacy-driven nature of post-millennial storytelling and its broader ideological implications. By exploring the intersection of platform media, participatory culture, and literary production, this paper sheds light on the evolving boundaries of storytelling in the age of platform capitalism. REZUMAT. Platformizarea povestirii: proză scurtă, imediatețe neoliberală și streaming de Twitch în România. În lumina ascensiunii neoliberale a capitalismului de platformă, narațiunea trece printr-o metamorfoză de neegalat, vizibilă chiar și în culturile semi-periferice, precum cea românească. Din punct de vedere metodologic, vom examina aceste transformări literare și culturale prin plasarea unui studiu de caz particular în cadrele ideologice ale capitalismului neoliberal așa cum se manifestă pe platformele de streaming. Studiul nostru de caz abordează emisiunea de pe Twitch și YouTube a lui reallyrux, „Cine-i janghina?”, unde spectatorii trimit scurte povestiri așa-zis autobiografice, având la bază teme prestabilite, axate pe conflicte plurivalente. Gazda citește și discută poveștile în cadrul live stream-urilor, evaluând în glumă stilul lor și sugerând în același timp că emisiunea îmbunătățește cunoștințele literare ale publicului, situând-o astfel atât ca divertisment participativ, cât și ca atelier informal. În consecință, scopul studiului nostru este triplu: în primul rând, să analizeze relația mutuală a literarului și digitalului, mai exact, a conținutului bazat pe platforme; în al doilea rând, să investigheze revitalizarea genului prozei scurte în contextul tendinței predominante a atelierelor de scriere creativă din România și a practicilor digitale participative; și, în al treilea rând, să evalueze natura imediateții povestirii post-mileniale și implicațiile sale ideologice mai ample. Prin explorarea intersecției dintre platformele media, cultura participativă și producția literară, această lucrare deslușește modul în care limitele narațiunii se dezvoltă în era capitalismului de platformă. Cuvinte-cheie: proză scurtă, autobiografie, social media, Twitch, Youtube, capitalism de platformă, neoliberalism, semi-periferie, Europa Centrală și de Est. Article history: Received 10 June 2025; Revised 20 August 2025; Accepted 30 August 2025; Available online 24 September 2025; Available print 30 September 2025.